Three-dimensional changes in temperature and circulation caused by northwestward-moving typhoons in a temperate semi-enclosed shelf sea in summer - Yanping Ma; Fangguo Zhai; Xingchuan Liu; Cong Liu; Zizhou Liu; Yanzhen Gu; Peiliang Li (Frontiers in Marine Science, 2025)
Due to the complex coastline and topography, changes of temperature and circulation in global shelf seas caused by typhoons have significantly region-specific three-dimensional structures. As one temperate semi-enclosed shelf sea, the Yellow Sea is highly susceptible to typhoons in summer. In August 2012 Typhoon Damrey moving northwestward over the Yellow Sea was observed to cause significant bottom temperature warming in the southern coastal waters of the Shandong Peninsula, but its impacts on the three-dimensional changes of temperature and circulation in the whole Yellow Sea and the underlying dynamics are still unclear. Using observations and high-resolution numerical simulations, we showed that during Damrey’s passage the South Yellow Sea exhibited spatially coherent surface cooling, particularly forming a distinct surface cooling band on the right side of the typhoon track. With the mixed layer deepening, the subsurface layer deepened and experienced temperature warming, especially on the right side of the typhoon track. The surface cooling and subsurface warming were primarily caused by strong wind-enhanced vertical mixing. In the deep layer, temperature exhibited pronounced warming in the southern coastal waters of the Shandong Peninsula but cooling in a southeast-northwest band along the bottom slope just off the Subei Shoal. Bottom temperature warming in the southern coastal waters of the Shandong Peninsula was caused by coastal downwelling resulting from upper layer coastward Ekman transport. Conversely, vertically consistent temperature cooling just off the Subei Shoal was caused by coastward and upward advection of cold water across the temperature fronts and thermocline due to surface layer Ekman divergence. The intensity and spatial distributions of temperature cooling just off the Subei Shoal were related to the distance between the typhoon track and Subei Shoal. Closer proximity of the typhoon track to the Subei Shoal would lead to more pronounced bottom cooling. This study enriches our understanding of three-dimensional hydrodynamic changes induced by typhoons with different tracks in the Yellow Sea.